The development of integrated regional economies in the Early Bronze Age Levant: new evidence from 'Combed Ware' jars. (3rd May 2020) - Badreshany, Kamal; Philip, Graham; Kennedy, Melissa
Abstract : This paper uses new petrographic and geochemical data (ICP-AES and -MS analyses) taken from samples of 'Combed Ware' jars occurring at sites on the Lebanese coast, the Bekaa Valley, the Orontes Valley around Homs and the North Jordan Valley, to investigate the production and distribution of these vessels in the Levant during the Early Bronze Age. The evidence points to the existence of integrated regional interaction zones that can be identified through specific modes of craft production and the associated distribution networks. The new evidence sheds light on the development of a nucleated settlement landscape, and the economic, social and political changes that this implies, in central Levant and western Syria during the first-half of the 3rd millennium BC, Early Bronze Age.